NORMATIVE AND LEGAL PROVISION OF THE SPATIAL PLANNING OF LAND USE DEVELOPMENT - Pyrih, А. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2023)
The text highlights the importance of comprehensive plans of territorial communities and the regulatory and legal support required to prepare them. It also reflects on the changes in land and urban planning legislation and provides recommendations for the creation of such plans. The comprehensive plan for the spatial development of the territory of the territorial community (hereinafter referred to as the comprehensive plan) is both urban planning documentation at the local level and land management documentation developed to ensure the sustainable development of the territory. The comprehensive plan provides for planning decisions regarding the prospective use of the entire territory of the territorial community, based on the analysis of all resources owned by the community, and provides the community with a tool for integrated development to solve problematic and conflict issues, as well as in compliance with the principle of balancing state, public and private interests. The comprehensive plan ensures coordinated decision-making regarding the integral (complex) spatial development of all settlements as a single settlement system and the territory beyond them. The main changes in the field of land and urban planning legislation, which are reflected in the Laws of Ukraine «On Urban Planning Activities», «On Land Management», the Land Code of Ukraine, as well as several other normative legal acts, resolutions of the Verkhovna Rada and the Cabinet of Ministers of Ukraine, are analyzed. It is proposed to improve the legislation on the use of land in the system of restrictions because significant territories can be removed from economic activity, which can reduce the income of local communities. It is also proposed to foresee the concept of «technological limitations» regarding more rational use of land by agro-enterprises and farms.